Historical Being in the Poetic Reception by S. A. Tuchkov: Array - Savoskina, Tatyana (Journal of Danubian Studies and Research, 2020)
The question of the poetic reflection of the lively socio-historical practice of Tuchkov, the military commander and founder of the Izmail - city, is considered in this article by his verses of various genres. Poetic works dedicated to the military and political events of the 18- th and 19-th centuries, creating an epic panorama of past epochs with their value-cultural, ideological and political priorities are analyzed here. Attention is focused on the thoughts of the lyrical subject, his reflective development of historical material in the paradigm of the odic traditions of Russian literature.